The house we grew up in [large type] - Jewell, Lisa (Thorndike Press, 2015)
The Bird family lives in a simple brick house in a picture-perfect Cotswolds village. Pragmatic Meg, dreamy Beth, and tow-headed twins Rory and Rhys attend the village school. Their father is a sweet gangly man, but it's their mother Lorelei, a beautiful free spirit, who spins at the center. Then a tragedy occurs and begins to tear the family apart. Years later, something calls them back to the house and to what really happened that Easter weekend.